Tipificación Genética de toxocara canis en la Zona Urbana de Latacunga - Peñaherrera Ordóñez, María Victoria (2019)
This research was carried out at Cotopaxi Province, in Latacunga urban area, the objective was to perform the Toxocara canis genetic classification. With identified owner, 60 domestic canines, both sexes, fecal matter samples, were collected. From 2 months to 9 years, age range, was the study population distributed of 3gr of fresh feces were taken, which were processed in the Laboratory of “Mundo Animal” Clinic Veterinary under the Sheather technique of flotation. Eleven canines were positive, detecting the presence of Toxocara canis eggs, which is (18.33%) of prevalence, according to the microscopic analysis by applying the qualitative technique (Crosses) to detect parasite eggs. The dogs population under study was dewormed orally, taking into account different living conditions and inadequate prophylactic control, the parasites expulsion in adult stage was observed in 21 canines, which represents 35% of the parasite's presence, based on the macroscopic diagnosis of fecal matter. In 9 canines from 2 to 4 months of age, deworming was performed without previous fecal analysis and as a result the parasite was expelled in the total number of animals, 100% of these parasites were identified as Toxocara canis based on the morphological characteristics they presented. It was determined that the microscopic technique is not fully effective if there is a low parasitic load or the parasites are in a different evolutionary stage. For the molecular typing of the adult parasite, the dissection was carried out following a standardized protocol for the Ascarididae family that includes Toxocara canis, guaranteeing the integrity of the biological sample to certify the extraction, titration and DNA quantification by avoiding the possible interference of the Reproductive organs during the DNA amplification process. From 30 samples in which Toxocara canis was morphologically identified, only 24 were confirmed as positive by PCR (80%), observing a correct amplification of bands, the remaining 20% could correspond to other types of toxocara, possibly Toxocara cati. The study demonstrates the high specificity in the diagnosis when using molecular tools